Effective Practices for Meeting the Learning Needs of ‘Superdiverse’ Multi-language Learners in Early Childhood Classrooms - Csillik Éva (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola-"RIK-U" Kft., 2020)
Abstract. The challenges of multilingual/multicultural education in our contemporary world are innumerable; therefore, there is an indispensable need for further inquiries and future research studies to propose in order to improve the quality of education in ‘superdiverse’ classrooms around the world. Since this field is still unexplored and in the need for immediate improvement, the author aims to widen one’s repertoire of effective teaching practices by sharing some of the author’s experiences as an English as a New Language teacher in New York City, in order to provide the best education possible for multilingual/multicultural learners in ‘superdiverse’ early childhood classrooms of today and in the upcoming future.

A mai világban a többnyelvű/multikulturális oktatás kihívásai szerteágazóak; ezért elengedhetetlen szükség van további vizsgálatokra és kutatási javaslatokra, amelyek elsősorban az oktatás minőségének javítását szolgálnák. Mivel ez a terület még korántsem teljesen feltárt, a szerző célja a hatékony tanítási gyakorlatok repertoárjának szélesítése, a szerzői tapasztalatok bemutatása, melyeket New Yorkban, angolnyelv-tanárként szerzett, hogy a többnyelvű/multikulturális tanulók számára elérhető legjobb oktatást tudjuk biztosítani.

Резюме. Виклики багатомовної/мультикультурної освіти в нашому сучасному світі незліченні; тому існує необхідність подальших досліджень, щоб покращити якість освіти по всьому світу. Оскільки ця сфера все ще не досліджена і потребує негайного вдосконалення, автор прагне розширити свій репертуар ефективної практики викладання, поділившись досвідом автора як вчителя англійської мови як нової мови в Нью-Йорку.
Hatékony osztálytermi gyakorlatok a „szuper-diverz” több nyelvet tanulók oktatási szükségleteinek összeegyeztetésére korai gyermekkorban
Ефективні практики в класі – «супер-дайверс» для узгодження освітніх потреб осіб, що вивчають різні мови, у ранньому дитячому віці
https://kmf.uz.ua/wp-content/uploads/2021/10/limes-2020-issue-vii_volume-1.pdf
https://opac3.brff.monguz.hu:443/hu/record/-/record/bibBRF00008905
Keywords: multilingual/multicultural learners; Early Childhood Classrooms; New York City; Superdiverse